2013
DOI: 10.5665/sleep.3230
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Variation of Heart Rate Variability Across Sleep Stages

Abstract: The circadian and sleep stage-specific effects on heart rate variability are clinically relevant and contribute to the understanding of the degree of cardiovascular vulnerability during sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
124
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(148 citation statements)
references
References 53 publications
19
124
1
4
Order By: Relevance
“…In both women and men, SE, SOL, ROL, TST, stage 1 sleep, stage 2 sleep, SWS, REM sleep, and/or NREM sleep significantly varied with time of day, as previously reported for a subset of participants (13)(14)(15) and with others who used imposed experimental non-24-h sleep-wake cycle procedures to desynchronize the sleep-wake and circadian cycles (16,17). The greatest and lowest sleep propensity occurred near the trough and crest of the CBT rhythm, respectively.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In both women and men, SE, SOL, ROL, TST, stage 1 sleep, stage 2 sleep, SWS, REM sleep, and/or NREM sleep significantly varied with time of day, as previously reported for a subset of participants (13)(14)(15) and with others who used imposed experimental non-24-h sleep-wake cycle procedures to desynchronize the sleep-wake and circadian cycles (16,17). The greatest and lowest sleep propensity occurred near the trough and crest of the CBT rhythm, respectively.…”
Section: Discussionsupporting
confidence: 54%
“…Each subject provided informed consent before participation. Each study had similar screening procedures, inclusion/exclusion criteria, prestudy sleep-wake schedule requirements, and baseline in-patient study conditions, as previously reported (13)(14)(15)37). None of our female participants were on contraceptives when we first contacted them during our recruitment procedures (see further details in SI Appendix, Methods).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been consistently shown that sympathetic activity is increased during rapid eye movement (REM) sleep and reduced during slow wave sleep (6,44,45). Fung et al (17) demonstrated a significant correlation between the percentage of slow-wave sleep and the incidence of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…6,15 On the other hand, there have been several evidence suggesting a relationship between circadian rhythm and car diac autonomic control. 22,23 Therefore, disturbance in circadian regulation may result in both sleepwake disturbance and OD. One more possibility may be that the occurrence of OD in a patient with CRSD is a presentation of a mere shift in the tim ing of normal orthostatic responses in CRSD, not a qualitative difference or pathological failure in the mechanisms of ortho static regulation.…”
Section: Discussionmentioning
confidence: 99%